Nocturnal Aphanistes (Hymenoptera: Ichneumonidae: Anomaloninae) in the Neotropical region, with the description of five new species - Alvarado, M. (Zootaxa, 2018)
The crepuscularis species group of the ichneumonid genus Aphanistes Förster currently comprises three species—Aphanistes crepuscularis Dasch, A. guatemalenus (Cameron), and A. arcei Gauld & Bradshaw. Five new species are described: A. augustoi sp. n., A. cachil sp. n., A. paolae sp. n., A. ruthae sp. n., and A. silviae sp. n. A key for the species group is also presented.